Effects of visitor numbers on captive European red squirrels (Sciurus vulgaris) and impacts on visitor experience. Issue 2 (21st February 2017) - Woolway, Eleanor E.; Goodenough, Anne E.
Abstract : Visitors to zoological collections can have substantial effects on captive animals that vary according to species, enclosure design, visitor proximity, and husbandry methods. One particularly intense form of visitor interaction occurs in immersive exhibits such as walk‐through enclosures. Such enclosures are increasingly common but effects on animal behavior are currently understudied. Here, the behavior of captive European red squirrels ( Sciurus vulgaris ) is studied in relation to visitor numbers in a walk‐through enclosure. We also quantify the correlation between squirrel encounters and visitor experience. Interaction with humans increased significantly as the number of visitors inside the enclosure increased. The number of children present significantly increased locomotion and decreased eating, possibly due to disturbance and squirrels moving away from busy areas. By contrast, the number of adults significantly increased eating and decreased inactivity due to squirrels approaching visitors. The positive reinforcement training used by the keepers (offering food rewards to the squirrels for coming to them to allow routine medical checks) meant that squirrels associated adults with food opportunities. Squirrel encounter rate (number of squirrels seen by each group of visitors) was significantly affected by the number of adults and visitor duration (positive relationships) and noise as perceived by visitors (negative relationship). Encounter rate was positively correlated with overall visitor experience. Our results indicate that visitors affect behavior but this effect is influenced by husbandry methods. It is vital that visitors, especially children, minimize noise, and move slowly in the enclosure, both for the sake of the animals and their own experience.